Peer victimization and adolescents' suicidal ideation and suicide attempts: A moderated mediation model. (May 2020) - Peng, Wenya; Li, Dongping; Li, Xian; Jia, Jichao; Wang, Yanhui; Xiao, Jiale
Highlights: Peer victimization (PV) was positively associated with adolescent suicidality. Psychological security (PS) partially mediated the impact of PV on suicidality. Family functioning exacerbated the relation between PV and PS among girls. Abstract: Suicide is the second leading cause of adolescent death. Research has established that peer victimization is a significant contributor to adolescent suicidal ideation and suicide attempts. However, relatively little is known about the mediating and moderating mechanisms underlying these relations. To fill this gap, this study constructed a moderated mediation model to examine whether psychological security mediated the relationships between peer victimization and suicidal ideation and suicide attempts, and whether these mediating processes were moderated by family functioning and gender. A total of 795 Chinese adolescents ( M age  = 14.41 years, SD  = 1.70) reported their demographic information, peer victimization, psychological security, family functioning, suicidal ideation, and suicide attempts. The results revealed that after controlling for demographic factors, peer victimization was positively associated with suicidal ideation and suicide attempts. Moreover, psychological security partially mediated the relationship between peer victimization and suicidal ideation and suicide attempts. Finally, family functioning moderated the relationship between peer victimization and psychological security in adolescent girls. Consistent with the reverse stress-buffering model, this negative relationship was stronger for girls with better family functioning. These findings highlight the importance of considering peer, family, and individual factors simultaneously to understand adolescent suicide when designing suicide prevention and intervention programs.